2021
DOI: 10.1111/josh.13052
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Health Literacy in Different Generations

Abstract: BACKGROUND:The development of health literacy (HL) is critical in reducing lifestyle-related diseases. The purpose of this study was to determine levels of HL and related variables among members of Generations X and Z. METHODS:This study was a descriptive survey conducted in the city of Antalya, Turkey. Participants were 350 Generation Z students and 150 Generation X parents. We created a personal data form for both students and parents, and used the Secondary Education HL Scale and Adult HL Scale for data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…For example, sports activities, eating less fast food and reading food labels were associated with higher nutrition literacy in adolescents 79. Furthermore, two studies assessed weight status and BMI as predictors of health literacy 49 70. In the first study conducted in Iran, higher BMI levels in senior high school students were correlated with higher functional nutrition literacy scores; however, this association was not significant after adjusting for the effect of other predictors in the multivariate analysis,70 and the other study in Turkey showed that this association was not significant either 49.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, sports activities, eating less fast food and reading food labels were associated with higher nutrition literacy in adolescents 79. Furthermore, two studies assessed weight status and BMI as predictors of health literacy 49 70. In the first study conducted in Iran, higher BMI levels in senior high school students were correlated with higher functional nutrition literacy scores; however, this association was not significant after adjusting for the effect of other predictors in the multivariate analysis,70 and the other study in Turkey showed that this association was not significant either 49.…”
Section: Resultsmentioning
confidence: 99%
“…The identified studies used various types of health literacy related to the following health topics: general health31 32 34 35 42–67; nutrition68–82; non-communicable diseases (NCDs)36 63; HIV83 84; e-health39 85–91; media92; physical health93 94; oral health38 95; medical96; disability67 97 98; mental health37 40 41 99–108; suicide109 110; and depression 33 111. These studies used 36 scales to measure health literacy, and these scales can be grouped into three categories: newly developed scales66 77 82 86 93 98; newly adapted and translated scales33 40 41 43 54 55 64 69 83 96 100 111; and previously adapted and translated scales 34 35 38 39 44–46 49 51–53 56–59 62 65 67 68 71–73 76 78–80 85 87–89 91 95 97 103 104 107–110 112 113…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations